2005
DOI: 10.1002/jcb.20599
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt antagonist secreted frizzled‐related protein‐1 controls osteoblast and osteocyte apoptosis

Abstract: Mechanisms controlling human bone formation remain to be fully elucidated. We have used differential display-polymerase chain reaction analysis to characterize osteogenic pathways in conditionally immortalized human osteoblasts (HOBs) representing distinct stages of differentiation. We identified 82 differentially expressed messages and found that the Wnt antagonist secreted frizzled-related protein (sFRP)-1 was the most highly regulated of these. Transient transfection of HOBs with sFRP-1 suppressed canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
113
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 69 publications
(115 reference statements)
7
113
2
3
Order By: Relevance
“…Further, our data indicate that sFRP-1 is also expressed highest in late osteoblasts, suggesting that this protein may also have a role in mechanotransduction similar to sclerostin by suppressing osteoblast activity and enabling the transition into an osteocyte. Notably, another group observed sFRP-1 peak expression during the transition from preosteoblast to osteoblast (Bodine et al 2005). Despite the early expression of this protein in the osteoblast ontogenesis, the authors observed a differentiation-inhibitory and proapoptotic role for sFRP-1.…”
Section: Discussionmentioning
confidence: 93%
“…Further, our data indicate that sFRP-1 is also expressed highest in late osteoblasts, suggesting that this protein may also have a role in mechanotransduction similar to sclerostin by suppressing osteoblast activity and enabling the transition into an osteocyte. Notably, another group observed sFRP-1 peak expression during the transition from preosteoblast to osteoblast (Bodine et al 2005). Despite the early expression of this protein in the osteoblast ontogenesis, the authors observed a differentiation-inhibitory and proapoptotic role for sFRP-1.…”
Section: Discussionmentioning
confidence: 93%
“…In humans, osteoporosis causes kyphosis through the deformity of the vertebral bodies (Cummings & Melton, 2002). The current concept suggests that osteoporosis represents a continuum with multiple underlying mechanisms contributing to loss of bone mass and mineral density and overall microarchitectural deterioration of bones (Ferrari et al, 2004;Tasker et al, 2004;Bodine et al, 2005;Horowitz & Lorenzo, 2007;Perrini et al, 2010). These factors are causally related to increased risk of falls, contributing to high incidence of fragility fractures in osteoporotic patients (Raisz, 2005;Ralston & de Crombrugghe, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Sfrp-1 increased with advancing osteoblast differentiation and peaked in the preostecyte stage [78]. Sfrp-1 −/− mice exhibit increased trabecular bone mineral density and volume.…”
Section: Secreted Frizzle Receptor Proteins (Sfrps)-sfrps Are Anothermentioning
confidence: 96%